The Role Of Leadership Principals In Developing Educational Institutions - Sirojudin Didin; Endha Lestari Evi; Chotimah Chusnul (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The principal is a functional teacher who is given the task of leading a school where the teaching and learning process is held. The principal as the leader of a formal educational institution has a very important role. The role of the head is as an educator, manager, administrator, supervisor, leader, innovator and motivator. The purpose of this research is to determine the role of school principals in developing educational institutions at Islamic Junior High School Al-Ikhsan Sawahan Jogoroto Jombang. In this research, researchers used qualitative descriptive analysis techniques, by exploring data from library research and field research. This research uses data collection methods through observation, interviews and documentation. Data analysis in this research uses qualitative descriptive analysis techniques. This method is used to systematically describe facts obtained from ongoing research on the object. The results of the research carried out were the Head of Islamic Junior High School Al Ikhsan Jogoroto Jombang has the ability and carries out his role as an educator, manager, supervisor, leader, innovator and motivator as well as overcoming various obstacles that exist in maintaining and developing Islamic Junior High School educational institutions Al Ikhsan Jogoroto Jombang, this can be seen by the increase in the number of students and increasingly developing both in terms of infrastructure and extracurricular activities.